A comprehensive review on clinically proven medicinal plants in the treatment of overweight and obesity, with mechanistic insights. Issue 2 (February 2023) - Aziz, Md Abdul; Millat, Md Shalahuddin; Akter, Tahmina; Hossain, Md Shahadat; Islam, Md Monirul; Mohsin, Shahriar; Ansari, Farzana; Kabir, Asma; Amin, Mohammad Nurul; Islam, Mohammad Safiqul
Abstract: Background and objectives: Obesity has become a global health issue, more precisely, a pandemic throughout the present world due to its high prevalence in the recent era. Increased risk of morbidity and mortality in obese patients can be attributed to its association with the development of different life-threatening conditions. Plants are considered one of the most important sources of bioactive molecules which are used against a wide range of health disorders. This systematic review explores the efficacy as well as the safety profile of commonly used medicinal plants in the management of obesity that may help people to maintain a healthy weight. Methods: This review is based on comprehensive literature searches from PubMed, Science Direct, Scopus, and Google Scholar databases using the keywords- "plants in obesity", "plants used in weight reduction" or keywords that are similar to those. Medicinal plants which have been clinically proven for their anti-obesity effect have only been selected for this study and attempts to investigate beneficial effects and adverse effects along with their mechanism of action have also been taken in this review. Results: A significant reduction of weight in both human and other animals are exhibited by the extracts of Phaseolus vulgaris, green coffee, Yerba Mate, green tea, Gynostemma pentaphyllum, and the combination of Cissus quadrangularis/Irvingia gabonensis. All of those plant extracts seemed to work on different physiological pathways and none of those extracts showed any notable adverse effects in human or animal models. Conclusion: Our review suggests that the discussed medicinal plants are effective in reducing the weight of obese patients without causing notable adverse reactions. Although further study is necessary to confirm their exact molecular mechanism and safety in human use.